3D amorphous carbon and graphene co-modified LiFePO4 composite derived from polyol process as electrode for high power lithium-ion batteries - Wu, G.; Ran, R.; Zhao, B.; Sha, Y.; Su, Chao; Zhou, Y.; Shao, Zongping (Elsevier Inc., 2014)
Amorphous carbon and graphene co-modified LiFePO4 nanocomposite has been synthesized via a facile polyol process in connection with a following thermal treatment. Various characterization techniques, including XRD, Mössbauer spectra, Raman spectra, SEM, TEM, BET, O2-TPO, galvano charge-discharge, CV and EIS were applied to investigate the phase composition, carbon content, morphological structure and electrochemical performance of the synthesized samples. The effect of introducing way of carbon sources on the properties and performance of LiFePO4/C/graphene composite was paid special attention. Under optimized synthetic conditions, highly crystalized olivine-type LiFePO4 was successfully obtained with electron conductive Fe2P and FeP as the main impurity phases. SEM and TEM analyses demonstrated the graphene sheets were randomly distributed inside the sample to create an open structured LiFePO4 with respect to graphene, while the glucose-derived carbon mainly coated over LiFePO4 particles which effectively connected the graphene sheets and LiFePO4 particles to result in a more efficient charge transfer process. As a result, favorable electrochemical performance was achieved. The performance of the amorphous carbon-graphene co-modified LiFePO4 was further progressively improved upon cycling in the first 200 cycles to reach a reversible specific capacity as high as 97 mAh·g−1 at 10 C rate.